Analisis Kelayakan Investasi Pembangunan Pasar Ikan Modern “Muara Baru”: Aspek Keuangan - Edy Supriyantony (LPPM STIE Bisnis Internasional Indonesia, 2023)
Directorate General of PDSPKP, Ministry of Maritime Affairs and Fisheries in order to improve competitiveness by increasing market facilities and infrastructure as the main chain of distribution of marine and fishery products, plans to build a world-class modern fish market (PIM). This research was conducted to know the feasibility of development from the financial aspects. The data were collecting with methods of field observation, interviews and literature studies. The results of the feasibility study of this plan show that PIM development is feasible to be implemented from the financial aspect. This is supported by the results of an analysis that shows 7.36 year payback period (PP) 7.36 year; NPV of Rp. 21.74 billion; IRR of 13.42%; and ROI of 21.91%.